IRE1α-XBP1 Affects the Mitochondrial Function of Aβ25–35-Treated SH-SY5Y Cells by Regulating Mitochondria-Associated Endoplasmic Reticulum Membranes - Chu, Bingcong; Li, Maoyu; Cao, Xi; Li, Rulong; Jin, Suqin; Yang, Hui; Xu, Linlin; Wang, Ping; Bi, Jianzhong (Frontiers in Cellular Neuroscience, 2021)
Background: Neurotoxicity induced by the amyloid beta (Aβ) peptide is one of the most important pathological mechanisms of Alzheimer’s disease (AD). Activation of the adaptive IRE1α-XBP1 pathway contributes to AD pathogenesis, making it a potential target for AD therapeutics. However, the mechanism of IRE1α-XBP1 pathway involvement in AD is unclear. We therefore investigated the effect of the IRE1α-XBP1 axis in an in vitro AD model and explored its potential mechanism. Methods: The human neuroblastoma cell line, SH-SY5Y, was used. Cells were treated with Aβ25–35, with or without 4µ8c, an inhibitor of IRE1α. Cells were collected and analyzed by western blotting, quantitative real-time PCR, electron microscopy, fluorescence microscopy, calcium imaging, and other biochemical assays. Results: The expression of XBP1s and p-IRE1α was increased in Aβ-exposed SH-SY5Y cells. MTT and calcium imaging analysis showed that the IRE1α inhibitor, 4μ8c, reduced Aβ-induced cytotoxicity. Increased levels of ATP, restoration of mitochondrial membrane potential and decreased production of mitochondrial reactive oxygen species after Aβ treatment in the presence of 4μ8c showed that inhibiting the IRE1α-XBP1 axis effectively mitigated Aβ-induced mitochondrial dysfunction in SH-SY5Y cells. Furthermore, Aβ-treatment increased the expression and interaction of IP3R, Grp75, and vdac1 and led to increased endoplasmic reticulum (ER)-mitochondria association and malfunction of mitochondria associated ER-membranes (MAMs) and mitochondrial dysfunction. These deficits were rescued by inhibiting the IRE1α-XBP1 axis. Conclusion: These findings demonstrate that Aβ peptide induces activation of the IRE1α-XBP1 axis, which may aggravate cytotoxicity and mitochondrial impairment in SH-SY5Y cells by targeting MAMs. Inhibition of the IRE1α-XBP1 axis protects against Aβ-induced injury in SH-SY5Y cells and may, therefore, be a new treatment strategy.